Competences of the university professor for the training of cyber-journalists - Peralta Ortiz, Vilma (2021)
The main objective of this research was to identify competencies that university professors require for the training of cyber-journalists. In this specific case, competencies were determined in three dimensions: technological, methodological and social. For this, it was carried out an exploratory-descriptive study, with a mixed approach and non-experimental transactional design. Two types of information collection instruments were used: a questionnaire that gathered the perspectives of 74 cyber-journalists from five media outlets, and an interview with 7 cyber-journalism specialists and professors. Results suggest the level of technological competence of the professor in order to training cyber-journalists should be between “advanced” and “expert”, which implies greater knowledge and practical use of somewhat unconventional technological resources used in cyber-journalism. It was also found that there is a need for university professors to be more committed to reorienting their teaching methodology to the reality of cyber-journalism. This implies (i) they frequently use technological resources in the classroom, having a greater impact over the practical rather than the theoretical issues; (ii) they should know where, when and how to use these resources; (iii) they must employ teaching methods based on cases, projects, practical demonstration and reflective dialogue in order to demonstrate knowledge and mastery of the course; (iv) they must plan their classes, in other words, do not improvise. Finally, regarding social skills, it is essential that university professor develops mainly communication, assertiveness, empathy and active listening.